RHINOMODELATION WITH HYALURONIC ACID: CASE REPORT - Carolina Marques de Oliveira, Adna; Barros da Cruz Brito, Mayara; Nunes Dantas, Ivanilda; de Freitas Lima, Rennaly; Galindo de Oliveira, Janaina; Belém Rodrigues Barros Soares, Vinícius; Gomes Moreira, Andréia (Health and Society, 2022)
The correction of imperfections in the nasal dorsum and attached structures with hyaluronic acid (HA) has become common because it is less invasive and a quick recovery procedure. Hyaluronic acid is the product of choice for rhinomodeling procedures, because it is moldable, it allows us to restructure the skin of the nose area, giving us immediate results, which can be reversed with the use of hyaluronidase. Given the above, this work aims to present a clinical case of rhinomodeling using hyaluronic acid. Female patient, sought care with a complaint regarding the tip of the nose, as she considered it “fallen”. To perform the rhinomodeling, we use hyaluronic acid at the points defined in the planning. Two orifices were used and the filled areas were the columella, base of the columella and the point of the nose. The patient was satisfied with the immediate result. It is concluded that rhinomodeling with hyaluronic acid provides immediate and satisfactory effects, being in the correction of small defects or improving the result of surgical rhinoplasties.